"You Think You Know Me, But You Have No Idea": Dynamics in African American Families Following a Son's or Daughter's Disclosure as LGBT. (April 2015) - Trahan, Don P.; Goodrich, Kristopher M.
This article describes a qualitative project, utilizing grounded theory, to explore the experiences of African American families when one member discloses their identity as lesbian, gay, or bisexual (LGB) or their gender identity as transgender (T). Respondents in this study included the LGBT-identified son or daughter, and a parent, to explore the impact of the disclosure process within African American families in the Southwestern United States. Implications for counseling practice and future research will be explored.